Galactose chicken intestinal absorption in vivo (Revista Española de Fisiología, 1974)
Galactose Chicken Intestinal Absorption in vivo. Rev. esp. Fistol., 30, 283-288. 1974.This work ineludes the possible research application in vivo method of successive absorptions in the chicken (Gallus domesticas) small intestine and the best experimental conditions to make it effective. The results indicate that this technique is also applicable to the study of the chicken sugar intestinal absorption.The galactose 2.77 mM absorption constancy found is considerable, at least during six successive 10 minutes periods. The active galactose transport by the chicken small intestine loops, shows a Michaelis-Menten kinetics with an apparent Km of 15.83 mM and a máximum absorption rate of 2 ¿unoles/cm intestine/10 min.The influence of the absorption time, repletion pressure, intestinal portion of máximum transport rate and animal age, has also been studied. The required conditions to obtain the best results have been 6 cm water repletion pressure, and intestinal loops prepared from central portions of the small intestine.The absorption rate differences in 2 to 4 week oíd chickens have not been significant.